PC based real-time audio signal processing - Faisal Ibne Jalal, Kamru; Parvez, Shahriar; Vhuiyan, Mamun (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.